The Impacts of India's Food Security Policies on South Asian Wheat and Rice Markets - Villoria, Nelson Benjamin; Mghenyi, Elliot Wamboka (Published by Oxford University Press on behalf of the World Bank, 2019)
We quantify the extent to which India's success in stabilizing its wheat and rice markets affects other countries in South Asia. We deal with the variability of Indian trade and price policies by analyzing market outcomes during periods of low and high world prices; we also conduct stochastic simulations where Indian policies endogenously adjust to fluctuations in domestic and world supplies. South Asian wheat and rice markets operate near autarky, and therefore, intra-regional price transmission is limited. However, we find that when India's policies result in implicit export subsidies, consumers in countries that import from India benefit; meanwhile implicit producer taxation harms consumers elsewhere. Pakistan—the only country in the region that competes with India in foreign markets—would see gains in market shares when India reduces its export subsidies. We also find that the low intra-regional trade shields India's neighbors from the excess volatility caused by Indian policies.